Analisis Pengaruh Literasi Keuangan Islam terhadap Inklusi Keuangan Syariah pada Generasi Milenial - Azizurrahman, Nur; Ruhadi; Suhartanto, Dwi (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2024)
Currently, there are still heated discussions regarding the low level of sharia financial literacy and inclusion, which causes a lack of competitiveness. At the same time, Indonesia is entering an era of demographic bonus, which can be seen from the large number of millennial generations and a Muslim population of 237.56 million people (86.7% of the total population). This research uses a quantitative approach with survey methods to collect data from a sample of the millennial generation in Indonesia. The research instrument is a questionnaire designed to measure the level of Islamic financial literacy and use of Islamic financial products and services. Data analysis was carried out using the SmartPLS tool to test the relationship between Islamic financial literacy and Islamic financial inclusion. The validity and reliability of the instrument were tested before data collection to ensure the accuracy of the research results. The research results show that there is a positive and significant relationship between Islamic financial literacy and Islamic financial inclusion. Millennials with a high level of Islamic financial literacy tend to be more active in using sharia financial products and services. This research has important implications for stakeholders, including governments, financial institutions, and educational organizations, to strengthen Islamic financial literacy programs to encourage wider participation in the Islamic financial system.